2016
DOI: 10.1016/j.eurpsy.2016.01.442
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the reductions in social interactions due to the economic crisis on the subjective well-being of non-insurance health care seekers in Greece

Abstract: BackgroundSocial interactions have an important effect on the subjective well-being of individuals. However, in periods of financial crisis these interactions are reduced, affecting thus the mental health of the individuals as well.AimTo investigate the effect of the reduction in social interactions, as a result of the economic crisis, on the subjective well-being of non-insurance health care seekers in Greece.MethodTwo hundred and sixty-six individuals participated in this study, 90 (35.6%) males and 163 (64.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…We found that fishermen's emotion regulation can improve their QoL in the context of a high PSS level. In this regard, it can be supposed that with a high level of PSS, fishermen can gain a sense of security, belonging, understanding, respect, and help from others (Lyrakos et al, 2016), which would be conducive to increasing their resources for coping with stress (Yalçín, 2011;Hofer, 2016). The amelioration of the negative effects of stress through such resources may thus be helpful for improving QoL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that fishermen's emotion regulation can improve their QoL in the context of a high PSS level. In this regard, it can be supposed that with a high level of PSS, fishermen can gain a sense of security, belonging, understanding, respect, and help from others (Lyrakos et al, 2016), which would be conducive to increasing their resources for coping with stress (Yalçín, 2011;Hofer, 2016). The amelioration of the negative effects of stress through such resources may thus be helpful for improving QoL.…”
Section: Discussionmentioning
confidence: 99%
“…The social background hypothesis of emotional regulation holds that the particular social context in which emotion regulation occurs, including social relationships that build external resources for emotional regulation, may weaken or enhance the influence of emotion regulation strategies on one's psychological response (Marroquín and Nolen-Hoeksema, 2015). According to this hypothesis, social relationships represent an important aspect of social support because they can help meet individuals' needs be met, affirm respect for beliefs, attitudes, and values, make people feel understood and cared for (Lyrakos et al, 2016), provide individuals with a sense of security, and become a conduit for increasing the resources individuals need to cope with stress, reduce psychological stress, and achieve personal growth (Hofer, 2016). In a high-PSS context, individuals should feel a sense of respect and understanding that can alleviate emotional imbalance and support emotional stability (Liao and Weng, 2018), thus helping to alleviate negative psychological problems while facilitating positive psychological changes (Collins and Feeney, 2000).…”
Section: Introductionmentioning
confidence: 99%